Label-Free Imaging of Female Genital Tract Melanocytic Lesions With Pump-Probe Microscopy: A Promising Diagnostic Tool. Issue 2 (April 2017) - Robles, Francisco E.; Deb, Sanghamitra; Fischer, Martin C.; Warren, Warren S.; Selim, Maria Angelica
Abstract : Objectives: Melanomas of the female genital tract present a unique clinical challenge. Not only are these lesions in an anatomically sensitive area, but also they tend to be multifocal and have high recurrence rates. Furthermore, several benign melanocytic proliferations resemble early-stage melanoma clinically and/or histopathologically. Thus, there is a significant need for additional tools that can help correctly diagnose and stage these lesions. Here, we quantitatively and nondestructively analyze the chemical composition of melanin in excised pigmented lesions of the female genital tract using pump-probe microscopy, a high-resolution optical imaging technique that is sensitive to many biochemical properties of melanin. Materials and Methods: Thirty-one thin ( 5 μm) tissue sections previously excised from female genital tract melanocytic lesions were imaged with pump-probe microscopy and analyzed. Results: We find significant quantitative differences in melanin type and structure between melanoma and nonmalignant melanocytic proliferations. Our analysis also suggests a link between the molecular signatures of melanins and lesion-specific genetic mutations. Finally, significant differences are found between metastatic and nonmetastatic melanomas. The limitations of this work include the fact that molecular information is restricted to melanin pigment and the sample size is relatively small. Conclusions: Pump-probe microscopy provides unique information regarding the biochemical composition of genital tract melanocytic lesions, which can be used to improve the diagnosis and staging of vulvar melanomas. Abstract : We analyze vulvar melanomas using an emerging optical molecular imaging technique called pump-probe microscopy. The method may improve the diagnosis and staging of vulvar melanomas. Supplemental digital content is available in the text.